Sustainability Of Small-scale Fishing Communities In Jaffna Peninsula Of Sri Lanka: A Multidimensional Analysis On Vulnerability - Gunaratne, Mahinda Senevi (2023)
Transboundary fishing between India and Sri Lanka is one of many issues that leads to vulnerabilities (classified as domains and drivers of vulnerability in the present study) in the human and natural environments of small-scale fishing (SSF) communities in Sri Lanka. Therefore, this qualitative study aims to (i) identify the factors that contribute to the vulnerability of SSF communities in the Jaffna peninsula in northern Sri Lanka, (ii) analyse how vulnerabilities impact SSF communities in the Jaffna peninsula in northern Sri Lanka, and (iii) devise intervention strategies that mitigate vulnerabilities and promote sustainability within SSF communities in Sri Lanka. A total of 25 respondents were involved in this study, including leaders of fisheries cooperative societies and other stakeholders in the SSF sector in the Jaffna peninsula. Primary data was collected through key informant interviews and focus group discussions and analysed following reflexive thematic analysis using ATLAS.ti software. The data analysis first identified multidimensional vulnerabilities deduced into 15 vulnerability drivers in five domains. The analysis found a new vulnerability domain in the Sri Lanka-specific context, i.e., the impacts of civil war and post-war torments. Analysis of the second objective suggests that all identified vulnerability drivers critically challenge the economic, environmental, and social sustainability of the SSF communities